2017
DOI: 10.1186/s40643-017-0181-5
|View full text |Cite
|
Sign up to set email alerts
|

Biofabrication of gold nanoparticles by Shewanella species

Abstract: Background: Shewanella oneidensis MR-1 (MR-1) and Shewanella xiamenensis BC01 (SXM) are facultative anaerobic bacteria that exhibit outstanding performance in the dissimilatory reduction of metal ions. Shewanella species have been reported to produce metal nanoparticles, but the mechanism and optimization are still not extensively studied and clearly understood. Herein, the effects of pH, biomass, gold ion concentration, and photoinduction are evaluated to optimize gold nanoparticle (Au@NP) production by Shewa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 43 publications
1
19
0
Order By: Relevance
“…Moreover, the hybrid organic-inorganic character of certain MOFs seems to favor the interaction of these materials with enzymes, since solid active biocatalysts can be formed by just contacting both species, even when the material does not contain enough large pores to host the enzyme [11]. Very different approaches to immobilize enzymes (more generally, proteins) on/in MOF materials have been recently developed and published elsewhere [26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45]. Some of them are based on the co-precipitation of the enzyme and the MOF material [26,28,29,[40][41][42][43][44] The exponential increase of the number of papers of enzyme@MOF biocatalysts certifies, on the one hand, the enormous interest of the scientific community in this subject and, on the other hand, the very favorable physicochemical interaction between MOF supports and the proteins.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the hybrid organic-inorganic character of certain MOFs seems to favor the interaction of these materials with enzymes, since solid active biocatalysts can be formed by just contacting both species, even when the material does not contain enough large pores to host the enzyme [11]. Very different approaches to immobilize enzymes (more generally, proteins) on/in MOF materials have been recently developed and published elsewhere [26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45]. Some of them are based on the co-precipitation of the enzyme and the MOF material [26,28,29,[40][41][42][43][44] The exponential increase of the number of papers of enzyme@MOF biocatalysts certifies, on the one hand, the enormous interest of the scientific community in this subject and, on the other hand, the very favorable physicochemical interaction between MOF supports and the proteins.…”
Section: Introductionmentioning
confidence: 99%
“…[20] Also, a similar report suggested immobilization of lipase, HRP (horseradish peroxidase), and catalase into ZIF-10, ZIF-8, and ZIF-90, respectively. [21] Further, researchers also have immobilized multiple enzymes within a ZIF-8 composite. [22] More recently, in situ synthesis of glucoamylase metal-organic framework was reported by a similar facile one-pot synthesis strategy.…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10][11][12][13][14][15][16][17] In this regard, enzyme-inorganic techniques such as conjugation, cross-linking and self-assembly hybrid nanomaterials produced by a variety of immobilization have received a significant attention because of their effectiveness to retain and stabilize enzyme activity. [18][19][20][21][22][23][24] Ge et al reported an innovative strategy to synthesize hybrid nanostructures having flower-like shapes (nanoflowers) based on the combination of enzyme molecules with metal salts in phosphate buffer. [25,26] The hybrid nanoflowers were more active and stable than conventionally immobilized enzymes owing to their large surface area and effective confinement of enzyme molecules in their core.…”
Section: Introductionmentioning
confidence: 99%